Cross-Reaction between the Crude Hydatid Cyst Fluid Antigens of Human and Animals Origin in Response to Human IgG Class and Subclasses. (13th March 2012) - Khosravi, Afra; Ghafourian, Sobhan; Shamsi, Morteza; Sadeghifard, Nourkhoda; Maleki, Abbas; Babaahmadi, Ebrahim
Abstract : The current work aimed to evaluate the cross-reactivity of human immune sera against crude hydatid fluid antigens of sheep, human, mouse, cattle, as well as B fraction of cystic fluid antigen. 30 balb/c mice were infected with sheep hydatid cyct fluid antigen containing protoscolex after the viability of these protoscolices was assessed. ANOVA was used to test the difference of themean of optical density (OD) values among case and control groups. The highest human IgG class antibody was against antigen B (0.93) and the lowest against cattle HCF antigen (0.32). The differences between responses to these antigens were statistically significant (P < 0.001 ). The sensitivity and specificity of ELISA test used for evaluating the responses of human total IgG to different hydatid cyst fluid (HCF) antigens among the case and control groups were 100 and 95.8%, respectively. Cross-reaction of human IgG class and subclasses responses was found almost for all the antigens with the best reaction against human and cattle (HCF) antigens and antigen B using a ratio of mean OD value to each antigen divided by the cut-off point value for the same antigen. Human sera showed a considerable cross-reactivity against all antigens by using ELISA.